PENGARUH METODE PEMBAYARAN COD TERHADAP MINAT PEMBELIAN PELANGGAN SHOPPE DI KALANGAN MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS KAPUAS SINTANG - magdalena, lin; Uca, Rosalina Farida (Universitas Kapuas Sintang, 2026)
This study aims to determine and analyze the influence of the COD (Cash on Delivery) payment method on purchase interest among Shopee customers among students of the Faculty of Social and Political Sciences at Kapuas Sintang University. Data collection was conducted using questionnaires, observation, and documentation. The population consists of students from the Faculty of Social and Political Sciences at Kapuas Sintang University. The sample size includes 53 respondents who are active students and users of Shopee COD. Analysis was calculated using the IBM SPSS Statistics 20 program. This research will conduct validity tests, reliability tests, simple linear regression hypothesis testing, correlation tests, t-tests, and coefficient of determination (R²) tests. The results of this study indicate that the instruments used for variables X and Y are declared valid because r-count > r-table and reliable because Cronbach's alpha (ɑ) for variable X = 0.850 and Y = 0.870, both greater than 0.6. The simple linear regression hypothesis test yielded the regression equation Y = 1.6804 + 0.442X. The correlation test results show a Pearson correlation value of 0.520, indicating that the COD payment method (X) and purchase interest (Y) fall into the moderate category (0.40 – 0.59). The t-test results indicate that t-count is greater than t-table (4.346 > 1.674), meaning that the COD payment method (X) has a significant influence on purchase interest (Y). The coefficient of determination test results show an R Square value of 0.256, meaning that the COD payment method influences 25.6% of the purchase interest among Shopee customers among students of the Faculty of Social and Political Sciences at Kapuas Sintang University, while the remaining 74.4% is influenced by other variables not examined in this study.